The great game will never end: Why the Global Financial Crisis is bound to be repeated - David Blake (Journal of Risk and Financial Management, 2022)
This article re-examines key explanations of the Global Financial Crisis-product complexity, behavioural biases in decision making, systemic risk, and regulatory arbitrage and capture-and finds a common underlying cause, namely gaming by personnel at all levels in the banking sector and its regulators. This has enabled banks to use highly leveraged, maturity-mismatched investment strategies, which were designed so that the banks retained the upside rewards, but transferred the downside risks to taxpayers, leading to the privatization of profits and the socialization of losses-behaviour that has been described as "banksterism". Although governments have introduced some significant mitigatory measures, they will not be effective in preventing future financial crises, because they do not and, indeed, cannot provide the appropriate incentives to end the Great Game between bankers and taxpayers, which would involve making bankers, rather than taxpayers, personally liable for losses.
Keywords: 650; behavioural biases; gaming; Global Financial Crisis; product complexity; regulatory arbitrage and capture; shadow banking; systemic risk